Lapisan Pemahaman Dan Folding Back Siswa Dalam Menyelesaikan Masalah Matematika Ditinjau Dari Adversity Quotient - Aviv Puji Indah Sari; Abadi Abadi; Atik Wintarti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aimed to provide a comprehensive detail of comprehension development within the Pirie-Kieren layers of understanding and the process of students folding students in resolving issues related to a two-variable linear equation system, focusing on the concept of adversity quotient. The research employed a qualitative descriptive approach. The data was collected on 36 students from class VIII-B at State Senior High School 2 of Taman. Within this sample, 6 students were selected, comprising of 2 students classified as having a high adversity quotient (referred to as “climber”), 2 students with a moderate adversity quotient (referred to as “camper”), and 2 students with a low adversity quotient (referred to as “quitter”). The study used problem-solving tests and interviews as data-gathering techniques, followed by data analysis techniques outlined by Miles, Huberman, and Saldana. The findings of this study indicated that the climber students demonstrated proficiency across all eight layers of understanding, as proposed by Pirie and Kieren. Climber students exhibited the process of folding back, which involved retrieving previously learned information to effectively address the current challenge without deviating from the relevant subject matter. On the other hand, camper students could attain a level of comprehension that extends to the structuring layer, albeit with a limitation in terms of the maximum attainable layer. However, it is essential to note that not all indicators of layer understanding may be attained flawlessly by camper students. Camper students underwent a process of folding back, delving into deeper layers, and gathering additional information to ensure the accuracy of their work. Quitter students could attain the image-making layer because they use inappropriate methods. However, suppose they employ a trial and error; the resultant value must satisfy two equations. Camper students experienced folding back, delving into more profound layers, and gathering deeper layers to ensure their work's accuracy.